The evaluation criteria for selecting the type of fixation implant for total hip replacement - V. N. Chornyi; A. P. Moskalkov; V. V. Malyshev (Zaporožskij Medicinskij Žurnal)
Osteoarthrosis is a chronic disease of joints. Endoprosthetics is one of the methods of treatment of osteoarthrosis. A choice of method of fixing of implant is one of the important questions in the preoperative planning. In a clinic «Motor-Sich» conducted the analysis of operative treatment of a 41 patients. The use of cortical index and criterias of ultrasonic densitometry is described in the choice of type of endoprosthesis.